Main Surgical Methods of Critical Tibial Bone Defects Replacement (Literature Review). Part II - Hrytsai, M.P.; Kolov, H.B.; Sabadosh, V.I.; Vyderko, R.V.; Polovyi, A.S.; НutsailiukV.I. (TERRA ORTHOPAEDICA, 2024)
Summary. This part of literature review is devoted to the main methods of critical bone defects replacement of the tibia, which cannot be repaired by using bone autoplasty. A search in the PubMed database for the period 2010 - 2023 was carried out, with preference given to the material from the last 5 years; the advantages and disadvantages of the most popular methods of treatment are shown. This article provides a descriptive, non-systematic review of the current literature on methods of tibial bone defect replacement and possible directions for future research. A thorough search in the PubMed database was performed using relevant search terms, with peer-reviewed articles in English identified and evaluated. No strict inclusion or exclusion criteria were used to select articles for a full-text review. Instead, a subjective assessment of the relevance of individual articles to the overall narrative and surgical techniques review was made, which ultimately resulted in 40 articles being referenced.